A new design and computer simulation of a 5-electrode ion extraction/focusing system - M. Medhisuwakul (2018)
A 13.56 MHz radio-frequency (rf) driven multicusp ion source has been constructed[1] to produce a high argon ion current density. Milliampere-range argon ion current can be extracted from the source. An in-waveguide microwave plasma source has been utilized as the ion beam neutralizer[2]. The neutralization source was placed 20 cm downstream from the extraction system. With the former extraction system, comprised of extraction electrodes and an Einzel lens, the electrons from the neutralizer were attracted to the high positive potential of the lens. Consequently, the potential of the lens drops and the beam is diverged. To suppress electrons from being accelerated to the Einzel lens a negatively biased electrode was placed before the last electrode, which is grounded, to produce a retarding electric field for electrons. The hole of the electrode was made small to make sure that the potential at the center is negative enough to suppress electrons. All simulations have been performed with the KOBRA3-INP simulation software. The results of the beam shape from the simulation will be presented. © 2005 Trans Tech Publications, Switzerland.